Ultrahigh performance concrete as radiation shielding with mixture of high density mineral - Masenwat, Noor Azreen (2019)
Radiation shielding linear attenuation coefficients μ (cm-1) is highly depends on the density of the material used. Previous studies have shown the mineral known as barite can be effectively used to increase the specific density of concrete structures. Barite in Malaysia is limited; therefore, a locally available alternative source must be identified to meet the requirements of high-density concrete for radiation shielding. With the aim to explore the possibilities, to be further developed for the application in the hot cell, radiation generating equipment and storing radioactive waste. This study selected steel fiber-reinforced ultra-high-performance concrete (UHPC) samples with different inert materials, namely, silica sand (2700kg/m3), amang (4000kg/m3), hematite (2967kg/m3), barite (4400kg/m3) and lead glass (3038kg/m3), as the study object and tested them experimentally for their mechanical properties and radiation absorption capabilities. The UHPC samples showed compressive strength values exceeding 155 MPa at 28 days. Meanwhile, UHPC with lead glass underwent decreased of compression strength in a long period, and UHPC with amang caused an issue related to radiological safety despite that it was effective as a γ-ray shield, UHPC with hematite and barite is very good in radiation absorption but cause an issue of practicality and country reserve. Thus, the use of UHPC with silica sand is practical for constructing nuclear facilities because of the abundance and cost-effectiveness of the involved materials.